2019
DOI: 10.1093/jpo/joz009
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking professionalization: A generative dialogue on CSR practitioners1

Abstract: Studies of emerging professions are more and more at the crossroad of different fields of research, and field boundaries thus hamper the development of a full-fledged conversation. In an attempt to bridge these boundaries, this article offers a ‘generative dialogue’ about the redefinition of the professionalization project through the case of corporate social responsibility (CSR) practitioners. We bring together prominent scholars from two distinct academic communities—CSR and the professions—to shed light on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 98 publications
1
49
0
3
Order By: Relevance
“…Within such domains, fragile and fragmented knowledge bases are co‐constructed together with new individual and organizational identities in ways that can threaten the power of established professionals on the consultant as well as on the client side (Bourgoin and Harvey ; Brès et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Within such domains, fragile and fragmented knowledge bases are co‐constructed together with new individual and organizational identities in ways that can threaten the power of established professionals on the consultant as well as on the client side (Bourgoin and Harvey ; Brès et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, our IRC framework could help understand the complex identity-power-knowledge dynamics that are at play when new, ill-defined domains, such as business ethics (Ben Khaled and Gond 2019), corporate social responsibility (Gond and Brès 2019), and sustainability (Hahn et al 2017), become subject to consultancy activities. Within such domains, fragile and fragmented knowledge bases are co-constructed together with new individual and organizational identities in ways that can threaten the power of established professionals on the consultant as well as on the client side (Bourgoin and Harvey 2018;Brès et al 2019).…”
Section: Opening Up Multiple Research Perspectivesmentioning
confidence: 99%
“…The article is based on the case of executive coaching and coaches, but this result is also found more broadly in "commercial" professions, mostly practiced by independent professionals such as real estate agents (Bernard, 2012), for whom the relationship to clients is crucial, both in the work itself and in the access to valued social positions. It suggests the need for further research, on other emergent corporate professions such as public relations (Reed, 2018) or corporate social responsibility practitioners (Brès et al, 2019), who already share many of the alternative conceptions of professionalization. The question of the relative weight of these new professionalization strategies and of the more classical ones must be assessed, to engage in the debate on the "changing nature of work" (Barley et al, 2017) and its effects on social morphology-although the answer depends on national context.…”
Section: Discussionmentioning
confidence: 99%
“…The template of "client professionalization" thus shows that professions are not doomed to be passive victims of marketization, just as showed that professions were not systematically compromised by their embeddedness inside large organizations. These strategies of a new kind can serve as indicators of the professionalization of emergent occupations (Brès et al, 2019) and they should be tested as such in further research on heterogeneity in professionalism.…”
Section: "Client Professionalization" Among "Corporate Professions"mentioning
confidence: 99%
“…Figure 1 shows where these discourses partially overlap or clash, and suggests potential frictions or alliances between their supporters, who can be viewed as distinct groups of CSR practitioners. We suggest opening up and closely scrutinizing distinct categories of CSR practitioners in future research, as the ideological and moral fragmentation of this emerging professional field may be revealed as even greater than previously assumed (Brès et al, 2019) once these practitioners' discourses are brought together and compared. Future research could leverage this insight and extend our analysis to a broader set of CSR practitioners across companies and industries (e.g., responsible investment, auditing) to clarify how distinct configurations of CSR practitioners promote specific moral views on CSR depending on the jurisdiction or field considered.…”
Section: Moral Compromise-making As Core To Csr Professionalism Micro-dynamicsmentioning
confidence: 99%